2018
DOI: 10.1177/1558944718787262
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pain Control in Upper Extremity Surgery: Prescribing Patterns, Recent Developments, and Opioid-Sparing Treatment Strategies

Abstract: The authors advise hand surgeons to utilize the strategies discussed in this review to assist in forming a unique, patient-specific postoperative analgesic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…This study also highlights the tendency for surgeons to overprescribe opioids following upper extremity surgeries, 16-22 as half of our patients did not consume any opioids. Patients consumed a mean of 5 tablets over the first 7 postoperative days, yet each patient received a prescription for 20 tablets.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This study also highlights the tendency for surgeons to overprescribe opioids following upper extremity surgeries, 16-22 as half of our patients did not consume any opioids. Patients consumed a mean of 5 tablets over the first 7 postoperative days, yet each patient received a prescription for 20 tablets.…”
Section: Discussionsupporting
confidence: 53%
“…These numbers are consistent with other studies in the literature, with mean postoperative opioid consumption numbers cited as 3.0 to 4.3 pills after carpal tunnel release. 18 Gauger et al 19 recently analyzed several articles on opioid use after upper extremity surgeries and found that surgeons tend to prescribe 2 to 5 times more opioids than patients actually consume. In a prospective evaluation of opioid consumption patterns, Kim et al 20 identified specific prescribing guidelines after they determined surgeons prescribed approximately 3 times the number of opioid pills consumed by their patients.…”
Section: Discussionmentioning
confidence: 99%
“…A perioperative multimodal analgesic regimen is recommended. 17 The authors prefer to position the patient in lateral decubitus with an arm post or in the supine position with a sterile padded Mayo stand. The bed is rotated 90° to facilitate intraoperative fluoroscopy and operating room setup.…”
Section: Surgical Technique: Im Screw Tbw Of Olecranon Fracturesmentioning
confidence: 99%
“… 29 Over the first decade of the 21st century, the opioid sales increased by 400%. 16 More recently, there has been a near 3-fold increase in the number of people with an opioid use disorder, 23 , 26 with the United States (US) making up 80% of the global opioid supply despite only representing 5% of the world’s population. 16 Most people’s first exposure to opioids is via prescription medication, 32 with many patients receiving prescriptions with the number of opioids well in excess of the number they will ultimately need to take for adequate pain control.…”
mentioning
confidence: 99%
“… 16 More recently, there has been a near 3-fold increase in the number of people with an opioid use disorder, 23 , 26 with the United States (US) making up 80% of the global opioid supply despite only representing 5% of the world’s population. 16 Most people’s first exposure to opioids is via prescription medication, 32 with many patients receiving prescriptions with the number of opioids well in excess of the number they will ultimately need to take for adequate pain control. 25 Orthopedic surgeons are among the leading prescribers of opiate medications, 23 and therefore, orthopedists have a substantial opportunity for improved opioid stewardship.…”
mentioning
confidence: 99%